IMPLEMENTASI PERATURAN BUPATI NOMOR 11 TAHUN 2021 TENTANG MAL PELAYANAN PUBLIK DI KABUPATEN KUBU RAYA - Iving Arisdiyoto; Dyan Safinah Ielma; Nawang Aviani; M. Ariy Darmawan S. (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2024)
The implementation of Public Service Malls to create integrated services in one place is one form of public service activity. Kubu Raya Regency is one of the regions that provides services through the Public Service Mall. This research aims to explain the process of implementing Regent Regulation Number 11 of 2021 concerning Public Service Malls, especially the benefits of Public Service Malls. Apart from that, identifying factors determining success and obstacles in the policy implementation process using Adam Smith's implementation theory. This research uses policy research methods by focusing on (1) identifying existing problems, (2) coordination between sectors related to the implementation of this regulation, especially at the One Stop Integrated Investment Service (DPMTSP) which has the authority to implement this regulation. And then on the participation of stakeholders, especially the community as the target group or target group, (3) Then evaluate the implementation of this regulation. The analysis technique used is descriptive analysis. The results of this research indicate efforts to achieve success in Public Service Malls as public service providers in order to create integrated services.